Peer Counseling Mentoring Model to Assist Students with Problems in Higher Education - Noviza, Neni; Khadijah, Nyayu; Darmawani, Evia; Kushendar, Kushendar; Makmum, Muh Ngali Zainal (COUNS-EDU: The International Journal of Counseling and Education, 2022)
This study aims to: (1) identify the factual conditions of guidance and counseling services that exist at the Faculty of Dakwah and Communication of UIN Raden Fatah Palembang, (2) analyze the problems experienced by students, (3) identify the needs of students for guidance and counseling services, ( 4) Knowing the process of developing a peer counseling guidance service model with a mentoring approach and (5) Producing an effective mentoring approach peer counseling service model following the objective conditions of the Faculty of Da'wah and Communication. This study uses a development approach (research & development). The population and research subjects were students, PA lecturers, BK lecturers, Deputy Dean III for student affairs and cooperation and guidance and counseling experts. Data collection tools in this study used interview guidelines and questionnaires. The results of the study show: (1) the factual condition of counseling guidance services at the Faculty of Da'wah and Communication is carried out by academic supervisors individually (45.14%), and group (42.44%) not good category (2) description of the problems experienced by students of the Faculty of Da'wah and Communication-based on the results of the AUM analysis of the most common problems experienced by BPI study program students in the field of career and work problems ( KDP) of 46.01%, and Personal Self (DPI) of 36.58% (3) students' need for guidance and counseling services is needed (86.98%) with reasons to help students solve/handle problems (9.44%), personal, academic, social, career and religious fields, students will take advantage of (52, 05%). 4) developing a model for peer counseling services by conducting preliminary studies, designing a hypothetical model, carrying out due diligence, improving the model, limited field trials, and perfecting the model. 5) The peer counseling guidance service model, the mentoring approach is effective 72.04%, in helping solve student problems at the Faculty of Da'wah and Communication at UIN Raden Fatah Palembang.